Knowledge level on administration of chemotherapy through peripheral and central venous catheter among oncology nurses - Sevgisun Kapucu; Ayşe Ozaydın Özkaraman; Neşe Uysal; Gulcan Bagcivan; Ferhan Cetin Şeref; Aygül Elöz (Elsevier, 2017)
Objective: The aim of this study is to determine the knowledge levels of oncology nurses about peripheral and central venous catheter during their chemotherapy administration. Methods: Data collection of this descriptive study was started on April 15, 2015-July 15, 2015. The data presented in this summary belong to 165 nurses. Data were collected with data collection form including questions related to sociodemographic qualifications and knowledge levels of nurses. Data collection forms were E-mailed to the members of Turkish Oncology Nursing Society. Data presented with numbers, percentages, and mean ± standard deviation. Results: The mean age of nurses was 33.60 ± 7.34 years and mean duration for oncology nursing experience was 2.65 ± 0.91 years. Nurses had correct information about the importance of selecting peripheral venous catheter and choosing the placement area for chemotherapy administration (63.6%), control of catheter before the administration (93.9%), influence of chemotherapeutic agent on length of catheter (40.6%), and management of extravasation (75.7%). Nurses also had correct information about the first use of port catheter (67.3%) and checking the catheter whether it is working properly or not (75.8%). Conclusions: In General, nurses' level of knowledge related to catheter is 50% and higher. It is recommended to increase the knowledge of nurses about evidence-based information for catheter care as a step to safe chemotherapy practice.